Clinical predictors of length of stay in adults with congenital heart disease. Issue 16 (25th February 2017) - Cedars, Ari; Benjamin, Lawrence; Burns, Sara V; Novak, Eric; Amin, Amit
Abstract : Objective: Length of stay (LOS) is a major driver of inpatient care costs. To date, few studies have investigated risk factors associated with increased LOS in patients with adult congenital heart disease (ACHD). In the present work, we sought to address this knowledge gap. Methods: We conducted an analysis of the State Inpatient Databases from Arkansas, California, Florida, Hawaii, Nebraska and New York. We analysed data on admissions in patients with ACHD and constructed a series of hierarchical regression models to identify the clinical factors having the greatest effects on LOS. Results: We identified 99 103 inpatient hospitalisations meeting criteria for inclusion. Diagnoses associated with the longest LOS were septicaemia (LOS=14.2 days in patients atrial septal defect, and 11.7 days among all other ACHD) and pericarditis, endocarditis and myocarditis (LOS=13.6 days and 10.0 days, respectively). When separated by underlying anatomy, the variables most consistently associated with longer LOS were bacterial infection, complications of surgeries or medical care, acute renal disease and anaemia. Conclusions: In the present study, we identified risk factors associated with longer LOS in ACHD. These data may be used to identify at-risk patients for targeted intervention to decrease LOS and thereby cost.